The Association between Major Dietary Pattern and Low Muscle Mass in Korean Middle-Aged and Elderly Populations: Based on the Korea National Health and Nutrition Examination Survey - Kim, Seong-Ah (Nutrients, 2020)
Reduced skeletal muscle mass in older populations is independently associated with functional impairment and disability, resulting in increased risk of mortality and various comorbidities. This study aimed to examine the association between major dietary pattern and low muscle mass among Korean middle-aged and elderly populations. A total of 8136 participants aged ≥50 years were included from a cross-sectional study based on the 2008–2011 Korea National Health and Nutrition Examination Survey. The following four distinct dietary patterns were derived using factor analysis: “Condiment, vegetables, and meats”; “wheat flour, bread, fruits, milk, and dairy products”; “white rice, fish, and seaweeds”; and “whole grain, bean products, and kimchi”. A higher “white rice, fish, and seaweeds” pattern score was associated with a lower prevalence of low muscle mass in both men and women, whereas a higher “condiment, vegetables, and meats” pattern score was associated with a higher prevalence of low muscle mass in men. A dietary pattern based on white rice, fish, and seaweeds can be helpful in protecting against loss of skeletal muscle mass in Korean middle-aged and elderly populations. Future research is paramount to confirm the causal association between dietary pattern and the risk of low muscle mass.